Cover Feature: Porous Molecular Capsules as Non‐Polymeric Transducers of Mechanical Forces to Mechanophores (Chem. Eur. J. 7/2020). Issue 7 (13th January 2020) - Jędrzejewska, Hanna; Wielgus, Ewelina; Kaźmierski, Sławomir; Rogala, Halina; Wierzbicki, Michał; Wróblewska, Aneta; Pawlak, Tomasz; Potrzebowski, Marek J.; Szumna, Agnieszka
Abstract : Molecular capsules can serve as stress‐sensitive units, which effectively transduce energy to mechanophores (here disulfide and hydrazone bonds). Upon mechanical treatment of empty capsules breakage of covalent bonds is induced, which enables complexation of large guests in covalent, otherwise non‐permeable capsules. Solid‐state NMR spectroscopy and solvent‐free MALDI experiments indicate that complexation takes place in the solid state and involves breakage of hydrazone and disulfide bonds. The same bonds present in non‐porous molecules are not activated under similar conditions. More information can be found in the Full Paper by M. J. Potrzebowski, A. Szumna, et al. on page 1558 .